Boosting Visible-Light Photocatalytic Hydrogen Evolution with an Efficient CuInS2/ZnIn2S4 2D/2D Heterojunction - Guan, Zhongjie; Pan, Jingwen; Li, Qiuye; Li, Guoqiang; Yang, Jianjun (ACS sustainable chemistry & engineering, 2019)
Developing photocatalysts with a high-efficiency charge separation remains a challenge in the solar hydrogen production. Herein, we devised and prepared a unique 2D/2D heterojunction of CuInS2/ZnIn2S4 nanosheets for solar hydrogen evolution. Structural characterizations reveal that the CuInS2/ZnIn2S4 2D/2D heterojunction with lattice match consists of the thin thickness of nanosheets and has a large interface contact area, boosting charges transfer and separation. Benefiting from the favorable 2D/2D heterojunction structure, the CuInS2/ZnIn2S4 2D/2D heterojunction photocatalyst with 5 wt % CuInS2 yields the highest H2 evolution rate of 3430.2 μmol·g–1·h–1. In addition, the apparent quantum efficiency of 5%CuInS2/ZnIn2S4 2D/2D heterojunction reaches 12.4% at 420 nm, which is high among the ZnIn2S4-based 2D/2D heterojunctions. The enhanced photocatalytic H2 evolution comes from the boosting charge separation. This work demonstrates that a 2D/2D heterojunction provides a potential way for significantly improving the solar hydrogen production performance of ZnIn2S4.